تطبق طريقة الرسم كالبديل لترقية مهارة الكتابة العرابية في مادة الخط بمدرسة مؤسسة المدرسة التربية الإسلامية الثانوية الأهلية سي توالانج راسو تنجون بالاي - Auliya Rahmadani Pardede; Usiono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Alkhat learning process at MTs S YMPI Sei Tualang Raso Tanjungbalai is not going well because many students still find it difficult to understand the material provided. This is known from the results of observations and interviews with students. Therefore, it is necessary to conduct research regarding the importance of learning the art of calligraphy in training students' Arabic writing skills at MTs S YMPI. The obstacles faced come from several factors, namely from students, teachers and schools. One method used by teachers to increase students' interest in learning Alkhat is through contemporary calligraphy or what is usually called the painting method. This research aims to determine 1) the effectiveness of the painting method in improving Arabic writing skills in the Al-Khat subject at MTs S YMPI. 2) How to implement the painting method in the students' Maharah Kitabah. 3) What are the results of the implementation of the painting method in the students' maharah kitabah? This research uses qualitative methods with a field study approach. Research data was collected through observation, interviews and documentation. The results of the research show that the painting method is effective in improving Arabic writing skills in the Al-Khat subject at MTs S YMPI. This is evidenced by an increase in students' motivation and interest in learning Al-Khat, as well as an increase in the quality of students' calligraphy written work. Apart from that, the painting method provides a fun and meaningful learning experience for students. This research contributes to the development of innovative and interesting Al-Khat learning methods. The painting method can be an alternative Al-Khat learning method that can increase students' interest and ability in writing Arabic.